IMPLEMENTASI PERATURAN DAERAH PROVINSI RIAU NOMOR 12 TAHUN 2002 TENTANG PEMBINAAN DAN PENGAWASAN PENYALURAN BAHAN BAKAR MINYAK OLEH PEMERINTAH KOTA PEKANBARU - Vera Magdalena Siahaan; Emilda Firdaus; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Fuel is a vital need for the community, this can be seen from the high level ofpublic demand for means of transportation, currently transportation is no longer aluxury item but a basic need. in everyday life the use of fuel both in industry andtransportation is increasing. With increasing demand, fuel is not supported bynatural resources and continues to decline, therefore management must be carriedout as optimally as possible. In view of this, to ensure the safety and availability offuel, it is necessary to carry out supervision. In this case, the central governmentthrough representatives of each region or local government, namely the PekanbaruCity Industry and Trade Service, supervises the distribution of fuel in PekanbaruCity. The Department of Industry and Trade of Pekanbaru City is the agencyresponsible for the technical implementation of guidance and supervision of thedistribution of fuel in accordance with regional regulation Riau Province Number 12of 2002 concerning guidance and supervision of the distribution of fuel. The practiceof selling retail fuel oil is prohibited by PT. Pertamina as the main distributor.However, judging from the facts on the ground, there are still many people who dothis by buying fuel oil using jerry cans, purchasing in this way is clearly prohibitedand regulated in the regional regulation of Riau Province Number 12 of 2002concerning guidance and supervision of the distribution of fuel to Article 6paragraph 1 "Each SPBU/PSPD and SPBB are prohibited from selling fuel tobuyers using drums, jerry cans and the like". This research will be structured usingthe type of legal sociological research, namely research that is said to be fieldresearch by examining applicable legal provisions and what happens in people'slives. The data collection technique in this study was a literature study followed byempirical data collection obtained from relevant agencies, as well as conductinginterviews to obtain information directly from informants. The results of the researchconducted by the author are first, every result of supervision can be used as animprovement in improving the quality of service quality. Second, even though thesupervision carried out was in accordance with the procedure, the violations thatwere committed still continued to occur. Not only from within, obstacles also occurfrom outside the management. Where the manager of fuel oil who has responsibilityin the buying and selling process does not understand the applicable rules, andresults in problems for many people (community).